ROBOTIC MONITORING SYSTEM – A COMPREHENSIVE REVIEW - Bharath; Prakash, R Om; M.D, S Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
Observation framework is the most import area in every one of the fields. The security framework ought to be more easy to use and compelling to make the checking tight and clean. Normal observing framework was finished by the assistance of CCTV camera which is fixed and has imperatives in review point also. Versatility of such reconnaissance is additionally not expectable. Subsequently security viability level lessening definitely which lead to average checking of the reconnaissance place. This paper kills the disadvantages of traditional papers and models. This undertaking thought manages the observing arrangement of any spot through a two or four wheeled ground vehicle (i.e.) a Robot fueled by an extremely ongoing little PC called Raspberry Pi Model. This task permits the checking framework by mean of both frame work administering just as a portable managing